2019
DOI: 10.1155/2019/3480512
|View full text |Cite
|
Sign up to set email alerts
|

Functional Brain Plasticity Associated with ACL Injury: A Scoping Review of Current Evidence

Abstract: Anterior cruciate ligament (ACL) injury is a common problem with consequences ranging from chronic joint instability to early development of osteoarthritis. Recent studies suggest that changes in brain activity (i.e., functional neuroplasticity) may be related to ACL injury. The purpose of this article is to summarize the available evidence of functional brain plasticity after an ACL injury. A scoping review was conducted following the guidelines of the Joanna Briggs Institute and the Preferred Reporting Items… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 79 publications
0
26
0
Order By: Relevance
“…15 Previous authors have aimed to better understand the cortical contributions to altered sensorimotor processing, potentially predisposing individuals to ACL injury risk 16 as well as protracted recovery following ACLR. 17,18 Research tools such as neuroimaging (functional magnetic resonance imaging [fMRI]) and transcranial magnetic stimulation (TMS) are commonly used to determine whole brain and motor cortex alterations respectively, after ACLR. Changes within the spinal cord are commonly measured using the Hoffmann Reflex (H-Reflex) which assesses the integrity of Ia afferent synaptic transmission contributing to the alpha motor neuron pool of the quadriceps within the anterior horn of the spinal cord.…”
Section: Nervous System Consequences Associated With Acl Injury and Reconstructionmentioning
confidence: 99%
“…15 Previous authors have aimed to better understand the cortical contributions to altered sensorimotor processing, potentially predisposing individuals to ACL injury risk 16 as well as protracted recovery following ACLR. 17,18 Research tools such as neuroimaging (functional magnetic resonance imaging [fMRI]) and transcranial magnetic stimulation (TMS) are commonly used to determine whole brain and motor cortex alterations respectively, after ACLR. Changes within the spinal cord are commonly measured using the Hoffmann Reflex (H-Reflex) which assesses the integrity of Ia afferent synaptic transmission contributing to the alpha motor neuron pool of the quadriceps within the anterior horn of the spinal cord.…”
Section: Nervous System Consequences Associated With Acl Injury and Reconstructionmentioning
confidence: 99%
“…We selected a lower bound age range of ~ 6 years old indicative of the age period in which youth generally exhibit the requisite motor competence to benefit from training/resistance/agility programs, possess sufficient level of physical and emotional maturity, and/or is ready for structured sports participation [10, 91-96, 98, 99, 105, 115]. An older bound age range of ~ 25 years old was included to be cognizant of the college-aged participants that constitute the majority of studies providing empirical data for the neuroplasticity of ACL injury [122] and OPTIMAL motor learning [160], yet still within the age window that is burdened by such musculoskeletal trauma [76,164]. However, we emphasize the described age window should not be considered fixed or restricted based on chronological number in light of various growth/maturational factors [9,97,104].…”
Section: The Solution: Optimal Prep Strategies For Injury Resistant Mmentioning
confidence: 99%
“…The recent proliferation of research into the neuroplasticity associated with ACL injury has revealed distinct alterations within the CNS (using methods including functional magnetic resonance imaging [fMRI], transcranial magnetic stimulation, etc.) (for a review see Neto et al [122]), providing an opportunity to apply innovative techniques capable of treating both movement and CNS dysfunction simultaneously in youth, such as OPTIMAL PREP strategies. To support the subsequent neurophysiologic sections related to ACL injury, Fig.…”
Section: Acl Injury and Neuroplasticity In Youth: An Overlapping Timementioning
confidence: 99%
See 1 more Smart Citation
“…A growing amount of evidence has begun identifying clinically meaningful neuroplastic changes in the sensorimotor system following ACL injury. Investigations utilizing transcranial magnetic stimulation, for instance, have detected enhanced motor thresholds in the ACL injured limb, whereas functional magnetic resonance imaging or electroencephalography (EEG) studies observed increased activations of the motor areas and lower activations of somatosensory areas in these patients (Neto et al, 2019). Along with altered somatosensory information from the ACL, decreased innervation to the primary sensory cortex (Valeriani et al, 1999), as well as different corticospinal and motor cortex excitability (Pietrosimone et al, 2015;Grooms et al, 2017;Lepley et al, 2020) have been observed in patients after ACL reconstruction.…”
Section: Introductionmentioning
confidence: 99%